Staphylococcus associated acute throat infection among children presented to a tertiary care hospital - Thattil, Santhosh John; Santhosh, Sumitha; Ajith, Thekkuttuparambil Ananthanarayanan (International Journal of Research in Medical Sciences, 2018)
Background: Staphylococcus infection remains one of the most common bacterial infections that cause high rate of morbidity and mortality in children and adults. This study was aimed to find the prevalent age group and type of Staphylococcus strain among the children presented with sore throat to a tertiary care hospital. Methods: A retrospective study was done by analyzing the medical records of children (less than 10 years of age) who presented to the outpatient Paediatric department with sore throat and confirmed diagnosis of Staphylococcus. Number of coagulase negative Staphylococcus (CoNS), Staphylococcus aureus (SA), methicilline resistant (MR) and methicilline sensitive (MS) strains was analyzed in various age groups and analyzed statistically. Results: Total 129 cases of Staphylococcus infected cases were found during the period of this study. The male to female ratio was 1.86 with high rate of prevalence found among the children of age 1-3 years (39.5%) (p= 0.0031). The CoNS was found in 65/129 (50.38%) cases and all were MSSA. No MRSA infection was found during the study period. Among the total cases, 122/129 (94.57%) cases were infected with MS strains. The MR strain was found in 7/129 cases (5.4%) which was mainly in neonates. The rate of infection was less in older children (7-10-year age). Conclusions: The prevalence of Staphylococcus associated throat infection was high among the children of 1-3-year age with male dominance. The MR strain was found only 5.4% of cases and no MRSA found in this study.